Role of Glycogen Synthase Kinase-3β in APP Hyperphosphorylation Induced by NMDA Stimulation in Cortical Neurons - Xanthi Antoniou; Gianluigi Forloni; Monica Di Luca; Fabrizio Gardoni; Mariaelena Repici; Alessio Colombo; Alessandra Sclip; Cristina Ploia; Tiziana Borsello (MDPI AG, 2010)
The phosphorylation of Amyloid Precursor Protein (APP) at Thr668 plays a key role in APP metabolism that is highly relevant to AD. The c-Jun-N-terminal kinase (JNK), glycogen synthase kinase-3β (GSK-3β) and cyclin-dependent kinase 5 (Cdk5) can all be responsible for this phosphorylation. These kinases are activated by excitotoxic stimuli fundamental hallmarks of AD. The exposure of cortical neurons to a high dose of NMDA (100 μM) for 30'-45' led to an increase of P-APP Thr668. During NMDA stimulation APP hyperphosphorylation has to be assigned to GSK-3β activity, since addition of L803-mts, a substrate competitive inhibitor of GSK-3β reduced APP phosphorylation induced by NMDA. On the contrary, inhibition of JNK and Cdk5 with D-JNKI1 and Roscovitine respectively did not prevent NMDA-induced P-APP increase. These data show a tight connection, in excitotoxic conditions, between APP metabolism and the GSK-3β signaling pathway.